2000
DOI: 10.1590/s0102-311x2000000700005
|View full text |Cite
|
Sign up to set email alerts
|

Classificação por ocupação dos casos de AIDS no Brasil - 1995

Abstract: Based on occupational classification of AIDS cases reported in Brazil in 1995 and recorded in the Data Base for Reported Diseases (SINAN), Pessoal (268,1), Cientistas Sociais (176,1), Escritores e Jornalistas (114,3), Auxiliares da Medicina e Odontologia (113,4), Químicos, Farmacêuticos e Físicos (111,9), Professores (87,3), Artistas (74,7), Serviços Portuários (65,6), Transportes Marítimos e Fluviais (57,5), Vendedores (55,4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
0
3
0
4
Order By: Relevance
“…Cabe considerar, por exemplo, que a informação sobre ocupação usada consta do banco de casos de AIDS do SINAN, codificada mediante as informações constantes na Ficha de Notificação de Casos de AIDS, que não contém instruções específicas de como definir a ocupação dos casos. Cassano et al (2000) relatam elevada proporção de casos com informação pouco específica sobre a ocupação, informada pelo SINAN/AIDS, como, por exemplo, "bancário", "autônomo", "funcionário público", "militar", impedindo sua classificação na categoria ocupacional correta na conversão para a Classificação de Ocupações do IBGE e elevando a proporção de casos classificados na categoria "ocupação mal definida".…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Cabe considerar, por exemplo, que a informação sobre ocupação usada consta do banco de casos de AIDS do SINAN, codificada mediante as informações constantes na Ficha de Notificação de Casos de AIDS, que não contém instruções específicas de como definir a ocupação dos casos. Cassano et al (2000) relatam elevada proporção de casos com informação pouco específica sobre a ocupação, informada pelo SINAN/AIDS, como, por exemplo, "bancário", "autônomo", "funcionário público", "militar", impedindo sua classificação na categoria ocupacional correta na conversão para a Classificação de Ocupações do IBGE e elevando a proporção de casos classificados na categoria "ocupação mal definida".…”
Section: Discussionunclassified
“…Para a análise das ocupações dos casos, procedeu-se à conversão das ocupações da CBO para a Classificação de Ocupações da Fundação Instituto Brasileiro de Geografia e Estatística (IBGE), proposta por Cassano et al (2000).…”
Section: Metodologiaunclassified
“…It is unclear why the managerial occupational group and those with secretarial or janitorial positions showed an increased proportion of AIDSrelated deaths as compared to other occupations in the Navy. Only a few studies have focused on occupational AIDS patterns 6,14,17 , and research with military populations did not address spe- Table 2 AIDS proportionate mortality and proportionate mortality odds ratio for the association between occupation and AIDS death in the Brazilian Navy, 1991-1995.…”
Section: Figurementioning
confidence: 99%
“…Noticeable, however, is the interaction with low rank, suggestive of an important role of hierarchy in sexual behavior in military institutions that needs to be addressed in future studies. Regarding occupation, a Brazilian study 17 reported increased cumulative AIDS incidence among personal care workers, social scientists, writers, journalists, physicians, dentists, chemists, pharmacists, physicists, teachers, artists, sales personnel, and workers in port services and maritime and river transport. Greater risk of HIV infection has been observed among workers exposed to blood, body fluids, and infected materials, such as surgeons 6 , laboratory workers 6,17 , and nurses 6 , common occupations in military settings.…”
Section: Occupationalmentioning
confidence: 99%
“…As ocupações foram classificadas de acordo com uma metodologia adaptada a partir de um modelo preconizado pelo sistema de Informações de Agravos de Notificação (SINAN) e a Classificação Brasileira de Geografia e Estatística (IBGE). 19 A primeira parte de caracterização da população foi construída e validada, utilizando um pré-teste com 10% da população.…”
unclassified